Layered zinc composite electrode, preparation method thereof and zinc ion battery
By forming a copper layer on the tin foil and then depositing zinc, a Sn/Cu/Zn layered composite electrode was prepared. The dendrite growth and hydrogen evolution problems of zinc negative electrode were solved by using the preferred deposition characteristics of the Cu substrate, and the high performance of zinc ion batteries was achieved. and long life.
Patent Information
- Application Number
- CN202411169172.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The existing zinc ion batteries have problems such as dendrite growth, passivation and hydrogen evolution during charging and discharging, resulting in failure of zinc negative electrodes and lack of zinc negative electrode materials for water-based zinc ion batteries with excellent performance.
The preparation method of layered zinc composite electrode is adopted, by immersing tin foil into a copper salt solution to form a copper layer, and then depositing zinc on the surface of the copper layer, the Sn/Cu/Zn layered composite electrode is prepared, and the preferential deposition characteristics of the Cu substrate are improved. Nucleation and electrochemical behavior of zinc.
It exhibits excellent electrochemical performance in symmetrical batteries and all batteries, extends the life of the negative electrode of zinc ion batteries and improves the practical application value of zinc ion batteries.
Smart Images

Figure CN119170727A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous rechargeable zinc ion batteries, in particular to a layered zinc composite electrode and a preparation method thereof and a zinc ion battery. Background Art
[0002] In recent years, multivalent ion batteries (such as Al 3+ Mg 2+ , Ca 2+ and Zn 2+ Batteries) have gradually attracted the attention of researchers, among which aqueous rechargeable zinc-ion batteries are favored due to their high safety, fast charging and discharging, and direct use of zinc metal negative electrodes. At present, the research on zinc-ion batteries is mainly focused on seeking high-performance positive electrode materials and their reaction mechanisms, while less attention is paid to the zinc negative electrode. During the continuous charging and discharging process, there are some problems with the zinc negative electrode, such as dendrite growth, passivation, and hydrogen evolution, which will lead to the failure of zinc-ion batteries. In order to solve these problems, researchers have proposed some strategies to optimize the zinc negative electrode, such as adding additives to the zinc negative electrode or electrolyte, and changing the microstructure of the zinc negative electrode. However, the deposition behavior of zinc on different metal surfaces may be different, and the metal substrate can significantly affect the electrochemical behavior of the zinc negative electrode, but currently little is known about the nucleation and plating / stripping behavior of zinc on various metal substrates, and there is a lack of zinc negative electrode materials with excellent performance for aqueous rechargeable zinc-ion batteries.
[0003] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0004] The invention provides a layered zinc composite electrode, a preparation method thereof and a zinc ion battery.
[0005] The present invention adopts the following technical solution:
[0006] In a first aspect, a method for preparing a layered zinc composite electrode is provided, comprising the following steps:
[0007] (1) immersing tin foil in a copper salt solution to form a layer of copper on the surface of the tin foil to prepare a Sn / Cu composite current collector;
[0008] (2) Immersing the Sn / Cu composite current collector in a zinc salt solution to form a layer of zinc on the surface of the copper layer, thereby obtaining a Sn / Cu / Zn layered composite electrode.
[0009] In a second aspect, a layered zinc composite electrode prepared by the preparation method described in the first aspect is provided.
[0010] In a third aspect, a zinc ion battery is provided, which includes a positive electrode, an electrolyte, a separator and a negative electrode, wherein the negative electrode is the layered zinc composite electrode described in the first aspect, or both the positive electrode and the negative electrode are the layered zinc composite electrode described in the first aspect.
[0011] The present invention has the following advantages: the Sn / Cu / Zn layered composite electrode prepared by the present invention exhibits excellent electrochemical performance in both symmetrical cells and full cells, has important guiding significance in the design and preparation of long-life zinc ion battery negative electrodes, and has important value in promoting the practical application of zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1a This is a flow chart of the preparation of the Sn / Cu / Zn layered composite electrode of Example 1 of the present invention;
[0013] Figure 1b The SEM image before and EDS image after zinc electrodeposition on the Ag|Cu bimetallic substrate;
[0014] Figure 1c The SEM image before and EDS image after zinc electrodeposition on the Ti|Cu bimetallic substrate;
[0015] Figure 1d The SEM image before and EDS image after zinc electrodeposition on Cu|Sn bimetallic substrate;
[0016] Figure 2a-2d They are respectively the nucleation overpotential curves of zinc deposited on a Cu substrate in Comparative Example 1, zinc deposited on an Ag substrate in Comparative Example 2, zinc deposited on a Ti substrate in Comparative Example 3, and zinc deposited on a Sn substrate in Comparative Example 4;
[0017] Figure 3a This is the result diagram of the interface binding energy between Zn and Cu, Ag, Ti, Sn and Zn obtained by DFT calculation;
[0018] Figure 3b is a TEM image of the Cu / Zn electrode obtained in Comparative Example 1;
[0019] Figure 3c yes Figure 3b Magnified image of the yellow dotted circle area in ;
[0020] Figure 3d yes Figure 3c HRTEM image and SAED pattern of the corresponding area (inset);
[0021] Figure 4a-4eThe graphs are the cycle performances of the corresponding symmetrical batteries of the pure zinc foil electrode, the Cu / Zn electrode in Comparative Example 1, the Ag / Zn electrode in Comparative Example 2, the Ti / Zn electrode in Comparative Example 3, and the Sn / Zn electrode in Comparative Example 4;
[0022] Figure 5a-5c The Cu / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, SEM image before cycle and SEM image after cycle;
[0023] Figure 5d-5f The Ag / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, SEM image before cycle and SEM image after cycle;
[0024] Figure 5g -5I are the Ti / Zn electrode in Comparative Example 3 at 1M Na 2 SO 4 LSV curve in electrolyte, SEM image before cycle and SEM image after cycle;
[0025] Figure 5j-5l The Sn / Zn electrode in Comparative Example 4 is 2 SO 4 LSV curve in electrolyte, SEM image before cycle and SEM image after cycle;
[0026] Figure 6a is a SEM image of the Sn / Cu composite current collector prepared in step (1) of Example 1;
[0027] Figure 6b is a SEM image of the Sn / Cu / Zn layered composite electrode prepared in Example 1;
[0028] Figure 6c is a voltage-time curve of zinc electrodeposition on the Sn / Cu composite current collector of Example 1;
[0029] Figure 6d is a SEM image of the Sn / Cu / Zn composite electrode after cycling in Example 1;
[0030] Figure 6e is the cycle performance of the Sn / Cu / Zn||Sn / Cu / Zn symmetric battery of the Sn / Cu / Zn layered composite electrode in Example 1;
[0031] Figure 6f is the cycling performance of the Cu / Sn / Zn||Cu / Sn / Zn symmetric battery of the Cu / Sn / Zn electrode in Comparative Example 5;
[0032] Figure 6g Yes V 10 O 24 ||Sn / Cu / Zn and V 10 O 24 ||Zn zinc ion battery cycling performance diagram. DETAILED DESCRIPTION
[0033] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other.
[0034] The specific embodiment of the present invention provides a method for preparing a layered zinc composite electrode, such as Figure 1a As shown, it includes the following steps:
[0035] (1) immersing tin foil in a copper salt solution to form a layer of copper on the surface of the tin foil to prepare a Sn / Cu composite current collector;
[0036] (2) Immersing the Sn / Cu composite current collector in a zinc salt solution to form a layer of zinc on the surface of the copper layer, thereby obtaining a Sn / Cu / Zn layered composite electrode.
[0037] In a preferred embodiment, the temperature of the copper salt solution in step (1) is 10-60° C. and the immersion time is 5-1000 seconds.
[0038] In a preferred embodiment, the copper salt solution contains a copper salt with a concentration of 0.1-2M and an acid with a concentration of 0.1-1M.
[0039] In a preferred embodiment, the copper salt is at least one of copper sulfate, copper chloride, and copper nitrate, and the acid is at least one of sulfuric acid, hydrochloric acid, and nitric acid.
[0040] In a preferred embodiment, step (1) is to immerse the tin foil in a copper salt solution, and to displace a layer of copper on the surface of the tin foil by a displacement method.
[0041] In a preferred embodiment, in step (2), the Sn / Cu composite current collector is immersed in a zinc salt solution to form a layer of zinc on the surface of the copper layer by electrodeposition.
[0042] In a preferred embodiment, the electrodeposition conditions in step (2) are: the electrolyte contains 0.1-3 mol / L ZnSO 4 7H 2 O, 0.2-1 mol / L Na 2 SO 4 and 0.2-2 mol / L H3 BO 3 , current density is 0.1-100mA / cm 2 , the electrodeposition time is 10-1000 seconds, and the temperature range is 0-60℃.
[0043] The specific embodiment of the present invention also provides a layered zinc composite electrode, which is prepared by the preparation method.
[0044] A specific embodiment of the present invention also provides a zinc ion battery, which includes a positive electrode, an electrolyte, a separator and a negative electrode, wherein the negative electrode is the layered zinc composite electrode, or both the positive electrode and the negative electrode are the layered zinc composite electrodes.
[0045] In a preferred embodiment, the zinc ion battery is a symmetrical battery, and its positive electrode and negative electrode are both the layered zinc composite electrode; or the zinc ion battery is a full battery, the positive electrode is vanadium oxide, and the electrolyte is a zinc salt aqueous solution.
[0046] like Figure 1b-1d As shown in the figure, Ag and Ti are electrodeposited on the surface of the metal Cu substrate, where the deposited metal area accounts for half of the copper foil area to obtain Ag|Cu and Ti|Cu. Half of the Sn foil is immersed in a Cu ion solution to prepare a Cu|Sn bimetallic substrate through a replacement reaction. Zinc is deposited on the prepared Ag|Cu, Ti|C, and Cu|Sn bimetallic substrates to compare the deposition behavior of zinc on the metals on both sides, as shown in the figure. Figure 1b-1d As shown, the results show that zinc is selectively deposited on the surface of the Cu substrate, and the deposition order of zinc on different substrates is Cu>Sn>Ti and Ag. By conducting zinc electrodeposition experiments on different bimetallic substrates (Ag|Cu, Ti|Cu, Cu|Sn), it is proved that zinc has the characteristic of preferential deposition on the Cu substrate, which provides an experimental basis for the subsequent design of the Sn / Cu / Zn layered composite negative electrode. The present invention is further described below by describing embodiments and comparative examples.
[0047] Example 1: Preparation of Sn / Cu / Zn layered composite electrode
[0048] The preparation of Sn / Cu / Zn layered composite electrode includes the following steps:
[0049] (1) Immerse the Sn foil in 0.94M CuSO 4 and 0.61MH 2 SO 4 The Sn / Cu composite current collector is obtained by placing the Sn / Cu composite current collector in the electroplating solution for 20 seconds without applying current.
[0050] (2) Electrodepositing a 10 μm thick layer of zinc on the obtained Sn / Cu composite current collector to obtain a Sn / Cu / Zn layered composite electrode. Specifically:
[0051] (2.1) The prepared Sn / Cu composite current collector was used as the working electrode, the platinum sheet as the counter electrode, and the Ag / AgCl electrode as the reference electrode.
[0052] (2.2) Immerse the electrode in a solution containing 62.5 g ZnSO 4 7H 2 O, 62.5 g Na 2 SO 4 and 10gH 3 BO 3 and 500 mL of deionized water zinc salt solution at 25 °C.
[0053] (2.3) At a constant current density of 40 mA cm -2 The electrodeposition was continued for 540 seconds.
[0054] (2.4) Take out the electrode, wash it with deionized water and ethanol, and then dry it to obtain a Sn / Cu / Zn layered composite electrode.
[0055] Comparative Example 1: Preparation of Cu / Zn Electrode
[0056] The copper foil was used as the substrate and zinc was replaced on its surface to produce a Cu / Zn electrode.
[0057] Comparative Example 2: Preparation of Ag / Zn Electrode
[0058] Silver foil was used as a substrate and zinc was replaced on its surface to produce an Ag / Zn electrode.
[0059] Comparative Example 3: Preparation of Ti / Zn Electrode
[0060] Titanium foil was used as a substrate and zinc was replaced on its surface to produce a Ti / Zn electrode.
[0061] Comparative Example 4: Preparation of Sn / Zn Electrode
[0062] Tin foil was used as a substrate and zinc was replaced on its surface to produce a Sn / Zn electrode.
[0063] Comparative Example 5: Preparation of Cu / Sn / Zn Electrode
[0064] Cu foil was used as the substrate, and a Cu / Sn / Zn electrode was prepared by electro-deposition of Sn and Zn.
[0065] 1. Battery assembly and testing
[0066] (1) Zn||Zn, Cu / Zn||Cu / Zn, Ag / Zn||Ag / Zn, Ti / Zn||Ti / Zn, Sn / Zn||Sn / Zn, Cu / Sn / Zn||Cu / Sn / Zn and Sn / Cu / Zn||Sn / Cu / Zn symmetrical cells were assembled using pure zinc, electrodes prepared in Comparative Examples 1-5 and Example 1, respectively. -2 The cycling performance was tested at different current densities.
[0067] (2) The electrodes prepared in Example 1 and pure zinc were used to assemble V 10 O 24 ||Sn / Cu / Zn and V 10 O 24 ||Zn full battery, at 1Ag -1 The cycling performance was tested at different current densities.
[0068] Specifically, V 10 O 24 , conductive carbon black and binder (PVDF) were mixed in a mass ratio of 7:2:1, N-methylpyrrolidone was added, and the mixture was stirred for 6-8 hours to prepare a slurry; the slurry was coated on a stainless steel foil and dried for 12 hours to obtain V 10 O 24 Positive electrode; V 10 O 24 The positive electrode, the Sn / Cu / Zn composite electrode prepared in Example 1 as the negative electrode or the pure zinc foil as the negative electrode, 2MZnSO 4 Electrolyte and glass fiber separator assembly V 10 O 24 ||Sn / Cu / Zn and V 10 O 24 ||Zn full battery.
[0069] 2. Representation and calculation
[0070] Scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy dispersive spectrum (EDS) and other methods were used to characterize the morphology and structure of the material; density functional theory (DFT) was used to calculate the binding energy between zinc and different metal substrates.
[0071] 3. Results
[0072] Figure 2a-2d is the nucleation overpotential curve of zinc on copper, silver, titanium and tin substrates, where Figure 2a is the nucleation overpotential curve of zinc deposition on the Cu substrate in Comparative Example 1, and the nucleation overpotential is 0 mV; Figure 2b is the nucleation overpotential curve of zinc deposition on the Ag substrate in Comparative Example 2, and the nucleation overpotential is 4 mV; Figure 2cis the nucleation overpotential curve of zinc deposition on the Ti substrate in Comparative Example 3, the nucleation overpotential is 200 mV; Figure 2d This is the nucleation overpotential curve of zinc deposition on Sn substrate in Comparative Example 4, and the nucleation overpotential is 70mV. Figure 2a-2d It can be seen that the nucleation overpotential of zinc on different metal substrates is different, and the deposition nucleation overpotential of zinc on the Cu substrate is the lowest, which indicates that zinc is more easily nucleated and grown on the Cu surface, further proving the advantage of Cu as a zinc negative electrode current collector.
[0073] Figure 3a-3d is the calculation result of the binding energy between zinc and different metals and the TEM characterization of the Cu / Zn interface, where Figure 3a The interface binding energy between Zn and Cu, Ag, Ti, Sn and Zn calculated by DFT is shown in Figure 2. The Zn-Cu interface binding energy is the highest (-0.22 eV), indicating that the interaction between Zn and Cu is the strongest. Figure 3b is a TEM image of the Cu / Zn electrode prepared in Comparative Example 1, where the interface between the Cu and Zn layers can be clearly seen, wherein the yellow dotted line indicates the interface between the Cu and Zn layers; Figure 3c yes Figure 3b A magnified view of the area with a yellow dashed circle in the figure; Figure 3d for Figure 3c High-resolution TEM (HRTEM) and selected area electron diffraction (SAED) images of the corresponding area (inset), showing that CuZn and CuZn 2 The lattice fringes of the alloy show that CuZn and CuZn are formed between the Zn and Cu layers. 2 Alloy. Figure 3a-3d It can be seen that zinc is preferentially deposited on the Cu substrate, which is beneficial to improve the stability and cycle performance of the Cu / Zn electrode.
[0074] like Figure 4a-4e The following are the cycling performances of different electrodes in symmetric batteries (at 0.5 mA cm -2 Current density, 0.5mah cm -2 The cycle performance is tested under the condition of cut-off capacity), where: Figure 4a Cycling performance of symmetric battery (Zn||Zn) with pure zinc foil electrode at 0.5 mA cm -2 After cycling for 55 h at the current density, the polarization voltage fluctuated dramatically, indicating that the cycling stability of the pure zinc electrode was poor. Figure 4b The cycling performance of the symmetrical battery (Cu / Zn||Cu / Zn) of the Cu / Zn electrode in Comparative Example 1 is shown in Figure 1 at 0.5 mA cm -2 The polarization voltage was stable at about 20 mV after cycling for more than 200 h at the current density, indicating that the Cu / Zn electrode has excellent cycling stability; Figure 4cThe cycle performance of the Ag / Zn||Ag / Zn symmetrical battery prepared in Comparative Example 2. The polarization voltage gradually increases during the cycle and fails after 150 hours. Figure 4d The cycling performance of the Ti / Zn||Ti / Zn symmetric battery prepared in Comparative Example 3 shows that the polarization voltage suddenly changes after 30 h of cycling, indicating that the cycling stability of the Ti / Zn electrode is poor. Figure 4e The cycle performance of the Sn / Zn||Sn / Zn symmetrical battery prepared in Example 4 is shown in Figure 4. The polarization voltage gradually increases during the cycle (from 10 mV to 20 mV), but is still below 20 mV after 200 h. Figure 4a-4e It can be seen that compared with pure zinc electrode and Ag / Zn and Ti / Zn electrodes, Cu / Zn electrode has better cycle stability, and Sn / Zn electrode also shows good cycle performance, which provides a reference for the design of Sn / Cu / Zn layered composite electrode. The composite electrode of the present invention shows an ultra-long cycle life in a symmetrical battery, which is more than 5 times that of a pure zinc foil negative electrode.
[0075] Figure 5a-5l The linear sweep voltammetry curves of different zinc electrodes and the SEM morphology after cycling, among which, Figure 5a The Cu / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, the potential of hydrogen evolution reaction is -1.96V; Figure 5b This is the SEM image of the Cu / Zn electrode before cycling in Comparative Example 1, where it can be observed that zinc in a layered structure is uniformly deposited on the surface of the Cu foil; Figure 5c The Cu / Zn electrode in Comparative Example 1 was -2 The SEM image after 50 h of cycling at the current density shows some irregular granular deposits on the surface; Figure 5d The Ag / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, the potential of hydrogen evolution reaction is -2.18V; Figure 5e This is the SEM image of the Ag / Zn electrode before cycling in Comparative Example 2. It is observed that the layered zinc is uniformly deposited on the surface of the Ag foil. Figure 5f The Ag / Zn electrode in Comparative Example 2 was -2 The SEM image after 50 h of cycling at the current density shows some irregular granular deposits on the surface; Figure 5g The Ti / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, the potential of hydrogen evolution reaction is -2.09V; Figure 5h This is the SEM image of the Ti / Zn electrode before cycling in Comparative Example 3, and the zinc deposition morphology is uneven; Figure 5i The Ti / Zn electrode in Comparative Example 3 was -2 The SEM image after 50 h of cycling at the current density shows some irregular granular deposits on the surface; Figure 5j The Sn / Zn electrode in 1M Na 2 SO 4 LSV curve in electrolyte, the potential of hydrogen evolution reaction is -2.25V; Figure 5k This is the SEM image of the Sn / Zn electrode before cycling in Comparative Example 4, where nanoflower-like zinc can be observed to be uniformly deposited on the surface of the Sn foil; Figure 5l The Sn / Zn electrode in Comparative Example 4 was -2 The SEM image after 50h of cycling at the current density shows that the surface morphology of zinc remains basically unchanged, and no obvious granular deposits appear. Figure 5a-5l It can be seen that the LSV test results show that the Sn / Zn electrode has the highest hydrogen evolution overpotential and can effectively inhibit the hydrogen evolution side reaction. The SEM image before cycling shows that the morphology of zinc on different metal substrates is different. The zinc on the Cu / Zn, Ag / Zn and Sn / Zn electrodes has a layered structure, while the zinc on the Ti / Zn electrode is relatively disordered. The SEM image after 50 hours of cycling shows that irregular layered particles appear on the surfaces of the Cu / Zn, Ag / Zn and Ti / Zn electrodes, while there is no obvious byproduct BZS on the surface of the Sn / Zn electrode. Therefore, there is no obvious byproduct BZS generation on the surface of the Sn / Zn electrode, and it has better electrochemical stability. That is, the Sn / Zn electrode can effectively inhibit the hydrogen evolution reaction and the generation of BZS, and has good electrochemical stability, which further verifies the feasibility of Sn as a zinc negative electrode current collector material.
[0076] Characterization and electrochemical performance test of Sn / Cu / Zn layered composite electrode Figure 6a-6f As shown, Figure 6a This is a SEM image of the Sn / Cu composite current collector prepared in Example 1. It can be seen that Cu is evenly covered on the surface of the Sn foil; Figure 6b This is a SEM image of the Sn / Cu / Zn composite electrode prepared in Example 1, from which it can be seen that the Zn layer is uniform and dense; Figure 6c The voltage-time curve of zinc electrodeposition on the Sn / Cu current collector in Example 1, wherein the nucleation overpotential is 0 mV; Figure 6d The Sn / Cu / Zn composite electrode in Example 1 at 0.5 mA cm -2 The SEM image after 50 h of cycling at the current density shows that no obvious BZS is generated, indicating that the Sn / Cu / Zn composite electrode has good structural stability and can improve the electrochemical stability of the Sn / Cu / Zn composite electrode; Figure 6eThe cycle performance of the Sn / Cu / Zn||Sn / Cu / Zn symmetric battery in Example 1 is shown at 0.5 mA cm -2 When cycling for more than 250 hours at a current density, the polarization voltage remains stable at 10mV for at least 250 hours, which is much better than the symmetrical battery with pure zinc foil electrode. Figure 6f The cycle performance of the symmetrical battery (Cu / Sn / Zn||Cu / Sn / Zn) of the Cu / Sn / Zn electrode prepared in Example 5 is shown in Figure 5 at 0.5 mA cm -2 When cycling for more than 200 h at the current density, the polarization voltage shows an upward trend; Figure 6g V prepared in Example 1 10 O 24 ||Sn / Cu / Zn and V 10 O 24 || Cyclic performance of Zn zinc ion battery. The results show that: V 10 O 24 ||The initial discharge capacity of the Sn / Cu / Zn battery is 184.6 mAh g -1 After 1000 cycles, the capacity remains at 130 mAh g -1 Above, the Coulombic efficiency is as high as 99.99%, that is, at 1Ag -1 After 1000 cycles at the same current density, the capacity retention rate and Coulombic efficiency are very high. In comparison, V 10 O 24 ||Zn battery has poor cycle stability, and its cycle life and capacity retention rate are lower than those of V 10 O 24 ||Sn / Cu / Zn battery. Figure 6a-6g It can be seen that the Sn / Cu / Zn composite electrode combines the advantages of Cu and Sn, and has good electrochemical performance and cycle stability. The performance of the Sn / Cu / Zn electrode in both symmetric cells and full cells is better than that of the pure zinc foil electrode and the Cu / Sn / Zn electrode, indicating its application prospects as an electrode material for aqueous zinc ion batteries.
[0077] The above examples show that due to the strong binding energy between Zn and Cu and the formation of CuZn and CuZn between the Zn and Cu layers, 2The alloy enables zinc to be preferentially deposited on the Cu substrate without nucleation overpotential, so that the Cu / Zn electrode has excellent cycle stability and reversibility. When Sn is used as a substrate, since metal Sn has a higher hydrogen evolution overpotential, it can inhibit the hydrogen evolution reaction, thereby reducing the generation of the byproduct basic zinc sulfate (BZS), and improving the electrochemical stability of the zinc electrode. Experimental results show that the Cu / Zn and Sn / Cu / Zn electrodes have excellent cycle stability, and the Sn / Zn electrode can inhibit the generation of the byproduct BZS. The Sn / Cu / Zn layered composite zinc electrode prepared by the present invention combines the advantages of Cu and Sn substrates and exhibits excellent electrochemical performance in symmetrical cells and full cells.
[0078] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing a layered zinc composite electrode, characterized in that , including the following steps: (1) immersing tin foil in a copper salt solution to form a layer of copper on the surface of the tin foil to prepare a Sn / Cu composite current collector; (2) Immersing the Sn / Cu composite current collector in a zinc salt solution to form a layer of zinc on the surface of the copper layer, thereby obtaining a Sn / Cu / Zn layered composite electrode.
2. The method for preparing a layered zinc composite electrode according to claim 1, characterized in that: The temperature of the copper salt solution in step (1) is 10-60° C.; the immersion time is 5-1000 seconds.
3. The method for preparing a layered zinc composite electrode according to claim 1, characterized in that: The copper salt solution contains copper salt with a concentration of 0.1-2M and acid with a concentration of 0.1-1M.
4. The method for preparing a layered zinc composite electrode according to claim 3, characterized in that: The copper salt is at least one of copper sulfate, copper chloride and copper nitrate, and the acid is at least one of sulfuric acid, hydrochloric acid and nitric acid.
5. The method for preparing a layered zinc composite electrode according to claim 1, characterized in that: Step (1) is to immerse the tin foil in a copper salt solution, and replace a layer of copper on the surface of the tin foil by a replacement method.
6. The method for preparing a layered zinc composite electrode according to claim 1, characterized in that: In step (2), the Sn / Cu composite current collector is immersed in a zinc salt solution to form a layer of zinc on the surface of the copper layer by electrodeposition.
7. The method for preparing a layered zinc composite electrode according to claim 6, characterized in that: The conditions for electrodeposition in step (2) are: the electrolyte contains 0.1-3 mol / L ZnSO4·7H2O, 0.2-1 mol / L Na2SO4 and 0.2-2 mol / L H3BO3, and the current density is 0.1-100 mA / cm 2 , the electrodeposition time is 10-1000 seconds, and the temperature range is 0-60℃.
8. A layered zinc composite electrode, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. A zinc ion battery, characterized in that: The invention comprises a positive electrode, an electrolyte, a separator and a negative electrode, wherein the negative electrode is the layered zinc composite electrode according to claim 8, or both the positive electrode and the negative electrode are the layered zinc composite electrode according to claim 8.
10. The zinc ion battery according to claim 9, characterized in that: The zinc ion battery is a symmetrical battery, and its positive electrode and negative electrode are both the layered zinc composite electrode according to claim 8; or the zinc ion battery is a full battery, the positive electrode is vanadium oxide, and the electrolyte is a zinc salt aqueous solution.
Citation Information
Patent Citations
Modified zinc metal sheet as well as preparation method and application thereof
CN114927632A
Aqueous zinc ion battery negative electrode material, preparation method and zinc ion battery
CN117542948A
Zinc negative electrode and battery
JP2014167910A
ZN powder / sn coated CU current collector as anode for ZN battery
US20220231278A1
